Proximity ligation assay for detection of R-Loop complexes upon DNA damage - Alagia, A; Ketley, RF; Gullerova, M (Springer, 2022)
In situ Proximity Ligation Assay (PLA ) can be used to detect the close proximity (less than ~40 nm) of two biological molecules of interest in cells. Here we report the application of this method for the specific detection of R-loop interacting proteins and RNA modifications in close proximity to R-loops in non-damage and ionizing radiation (IR) induced DNA damage conditions.